Effectiveness of AutistAR to enhance communication and social skills among children with autism - Hushairi, Natasha Amira; Mohamad Ashari, Zakiah; Yeo, Kee Jiar; Handayani, Lina (International Journal of Evaluation and Research in Education (IJERE), 2024)
Individuals diagnosed with autism spectrum disorder (ASD) may have serious fundamental deficits in communication, social, inventiveness, and constructive skills. In the age of technology, children with disabilities frequently employ assistive technologies to aid in their learning and support the rehabilitation process, particularly for autism. Individuals with ASD require technology-based tools such as software or applications that could assist them with communication, language, organizing skills, and information processing. This research developed an augmented reality (AR) application integrating picture exchange communication systems (PECS) to aid children’s communication and social skills. A single-case experimental design (SCED) method was used to analyze the features and effectiveness of AutistAR. The study included a sample of two individuals diagnosed with ASD, characterized by restricted communication and social abilities. The result revealed that there was an improvement in overall communication and social skills in both participants. The ramification of the findings is further explored.